Linac-integrated on-board spectral-CT/CBCT imaging using a photon-counting detector: a Monte Carlo study - Ye, Fengsong; Wang, Hui; Fang, Jianqiang (Frontiers in Physics, 2023)
Purpose: To investigate the feasibility of dual-modal on-board spectral-CT/CBCT imaging using a CZT photon-counting detector mounted on a Linac by Monte Carlo simulations. Methods: In this proof-of-concept study, the Monte Carlo software platform of Geant4 Application for Tomography Emission (GATE) and a high-performance computing hardware platform were utilized to design and validate the novel on-board spectral-CT and conventional CBCT imaging system using a single CZT detector integrated into a Linac. Through the combined use of the Monte Carlo simulation and the charge transportation model based on a diffusion equation, we simulated x-ray energy spectra of the CZT detector with pixel sizes ranging of 200–1,000 μm, based on which the optimized pixel size of the detector was determined. Spatial resolution of the CBCT imaging of the system was evaluated by oversampling a tilted tungsten wire. A PMMA phantom, containing calcium and contrast elements of iodine, gadolinium, and gold, was simulated to demonstrate the spectral CT imaging capability of the system by using the K-edge spectral imaging method. Results: Considering the trade-off between the photon-peak efficiency and spatial resolution of the detector, the pixel size of the CZT detector was determined to be 400 µm. The spatial resolution of the CBCT imaging of the system was estimated to be 19.2 lp/cm@10% modulation transfer function. The CBCT imaging of the system provided sufficient structural details of the phantom with a high image contrast. Compared to the CBCT image of the phantom, the K-edge spectral CT images differentiated the four elements contained within the phantom very well. Conclusion: The simulation results demonstrated the feasibility of dual-modal on-board spectral-CT/CBCT imaging by using a single CZT photon counting detector in a Linac.